The Histopathological Types and Distribution Characteristics of Gastric Mixed Tumors - Zhu, Fang-Heng; Wang, Yang-Kun; Zhou, Jun-Ling; Meng, Nian-Long; Wang, Yue; Jiang, Bo; Wang, Su-Nan (Frontiers in Oncology, 2022)
Objective: The present study aimed to investigate the histopathological types and distribution characteristics of gastric mixed tumors. Methods: Detailed histological observations, together with related immunohistochemical and genetic tests, were analyzed on 960 surgically resected samples in 6 hospitals with gastric mixed tumors from May 2017 to May 2021 in this retrospective study. Results: Epithelial-derived tumors accounted for 80.10% (769/960) of the gastric mixed tumor samples studied, and tumors of different tissue origins accounting for 10.83% (104/960), mesenchymal-derived tumors accounting for 6.25% (60/960), neuroendocrine tumors accounting for 2.40% (23/960), and lymphoma accounting for 0.42% (4/960). The histological types of gastric mixed tumors identified as most commonly were epithelial originated, followed by mixed tumors of different tissue originated, then mixed neuroendocrine, lymphoma, and mesenchymal originated in sequence. The histological number of gastric mixed tumors was ≤ 3 in 83.23% (799/960) of cases and > 4 in 16.77% (161/960) of cases. The mixed histological patterns of gastric mixed tumors were divided into three types: those with tumor cells interspersed with each other, those with incomplete fibrous tissue separation, and those without fibrous tissue separation. The gene target characteristics of gastric mixed tumors were the existence of multi-gene mutation, including human epidermalgrowth factor receptor-2 (HER2) gene amplification, key result areas (K-ras) and platelet-derived growth factor receptor alpha (PDGFRA). Conclusion: Gastric mixed tumors should be adequately sampled, each piece of tissue should be involved in the morphological proportional division of the tumor, and any independent histological component should be written into the pathological examination report.